The influence of regional original income, general allocation funds, special allocation funds, and capital expenditures on the financial performance of regional governments in Indonesian Provinces (2017-2021) - Dandi Tumanggor; Fadli (Jurnal Mantik, 2023)
The level of effectiveness of regional governments in managing regional finances, especially the Regional Revenue and Expenditure Budget (APBD), can be seen from their financial performance. If the local government's financial performance is high, it shows that financial management performance can be said to be successful . This research was conducted in order to determine the relationship between the realization of local original income, special allocation funds, general allocation funds, and capital expenditure on the financial performance of regional governments in 33 provinces in Indonesia. This research data comes from the APBD realization report for each province which has been audited by the central BPK for 2017-2021. The research findings show that when viewed individually, both the realization of regional income from special allocation funds and capital expenditure have a positive and significant effect on the fiscal performance of regional governments in 33 provinces in Indonesia. However, it needs to be emphasized that general allocation funds do not have a significant impact on regional government financial performance. The combined impact of PAD, DAU, DAK, and capital expenditure simultaneously influences the financial performance of local governments in 33 provinces in Indonesia